Spontaneous preputial cavity abscess : a rare case report - Dutta, Somnath; Das, Uddalok (The ESRF Research Journal for Undergraduate Medical Students, 2023)
Spontaneous preputial cavityabscess is a rare presentation. Pus collects between the penile shaft and overlying skinwithout involving the penile muscles or urethra.The condition is acknowledged to be rare, so the importance of recognitionand appropriate treatment is important. This is especially true for penile pathology where patients are often reluctant todisclose relevant signs and symptoms.We present a case of spontaneous preputial cavity abscess that was diagnosed andtreated at our institution.